MOBILITY GAMES: PLAYING AND LEARNING FOR THE CHILD’S HOLISTIC DEVELOPMENT (CIPEEX, 2025)
Introduction: Childhood is a time marked by motor, cognitive, social, and emotional development. Mobility games, which are playful activities centered around body movement, play a key role in this process because they help develop motor skills and encourage social interaction. Objective: To explore how mobility games can support the overall development of children. Method: This is a literature-based study, based on a review of scientific articles that connect play, learning, and the promotion of child development. Results: The findings show that mobility games help improve coordination, balance, creativity, social skills, and independence. They also stimulate cognitive and emotional growth, bringing together physical and emotional aspects in the learning process. Conclusion: Mobility games should be encouraged both in educational and health settings, as they support holistic development and help prepare children for social interactions and school life in a fun and healthy way.
Keywords: Learning; Childrem; mobility games; playful activities